2020
DOI: 10.1177/1758835920923829
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of GDPT (gemcitabine, cisplatin, prednisone, thalidomide) versus CHOP in newly diagnosed peripheral T-cell lymphoma patients

Abstract: Aim: To compare the outcomes of GDPT [gemcitabine (G), cisplatin (D), prednisone (P), thalidomide (T)] versus CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) in treating newly diagnosed PTCL (peripheral T-cell lymphoma). Methods: An open-label prospective clinical trial with 153 newly diagnosed PTCL patients conducted between January 2010 and December 2018 was designed. Patients were randomly assigned to the GDPT (77 cases) and CHOP (76 cases) groups. Patients in each group were further divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…As it is less toxic than CHOP, it could be used for this type of patient [ 66 , 67 ]. Recently, a GDPT regimen, i.e., GDP added to thalidomide, has shown to be a new promising approach to treat patients with relapse and refractory PTCL including ALK(+)ALCL [ 68 ]. Indeed, GDP, composed of Gemcitabine (an antimetabolite), Cisplatin (an alkylating agent) and Prednisone, was previously used to treat relapsed or refractory patients affected by Peripheral T-cell lymphoma (PTCL), including ALCL.…”
Section: Chemotherapymentioning
confidence: 99%
“…As it is less toxic than CHOP, it could be used for this type of patient [ 66 , 67 ]. Recently, a GDPT regimen, i.e., GDP added to thalidomide, has shown to be a new promising approach to treat patients with relapse and refractory PTCL including ALK(+)ALCL [ 68 ]. Indeed, GDP, composed of Gemcitabine (an antimetabolite), Cisplatin (an alkylating agent) and Prednisone, was previously used to treat relapsed or refractory patients affected by Peripheral T-cell lymphoma (PTCL), including ALCL.…”
Section: Chemotherapymentioning
confidence: 99%
“…In the rare prospective upfront setting, a recent trial of 153 patients was reported demonstrating superiority of GDPT (gemcitabine, cisplatin, prednisone, and thalidomide) versus CHOP in previously untreated patients with PTCL, with respect to ORR (66.3% vs. 50.0%, p = 0.042), CR rate (42.9% vs. 27.6%, p = 0.049), 4-year PFS (63.6% vs. 53.0%, p = 0.035), and 4-year OS (66.8% vs. 53.6% for OS, p = 0.039). There were no differences in measured adverse effects between the two cohorts, with myelosuppression being the most common grade 3 or 4 AE [93].…”
Section: Immunomodulatorsmentioning
confidence: 86%
“…In a multicenter phase II study, Azacitidine and Romidepsin achieved an ORR of 80% (12/15) and a CRR of 60% (9/15) in T-FHCL patients. Our center has also conducted multiple clinical trials ( 25 , 26 ) showing promising results with certain regimens, such as “GDPT” (gemcitabine, cisplatin, prednisone, thalidomide) and “C-PET” (chidamide plus prednisone, etoposide, and thalidomide), which significantly improved disease remission rates and prolonged disease remission duration in nTFHL patients. Furthermore, ongoing research on the new regimen “ Das + AZA + CEP “ (Dasatinib, Azacitidine, Etoposide, Cyclophosphamide, Prednisone) for AITL treatment and the exploration of other new regimens aim to further enhance the therapeutic efficacy of this disease family.…”
Section: Discussionmentioning
confidence: 99%